2022
DOI: 10.3390/cancers14215201
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Quantitative CT Analysis in RANKL Expression of Spinal GCTB in the Denosumab Era: A Machine Learning Approach

Abstract: The receptor activator of the nuclear factor kappa B ligand (RANKL) is the therapeutic target of denosumab. In this study, we evaluated whether radiomics signature and machine learning analysis can predict RANKL status in spinal giant cell tumors of bone (GCTB). This retrospective study consisted of 107 patients, including a training set (n = 82) and a validation set (n = 25). Kaplan-Meier survival analysis was used to validate the prognostic value of RANKL status. Radiomic feature extraction of three heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Our study confirmed this association, as the radiomics scores derived from planning CT images were significantly higher in the pCR group, with all corresponding AUC values being greater than or nearly 80%. While some studies favored SVM classifiers over the LASSO or RF methods [32][33][34][35] in the development of radiomics models, other studies reported the superior performance of the LASSO or RF classifiers [27,[36][37][38][39]. These divergent findings suggest that the choice of machine learning model influenced the predictive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed this association, as the radiomics scores derived from planning CT images were significantly higher in the pCR group, with all corresponding AUC values being greater than or nearly 80%. While some studies favored SVM classifiers over the LASSO or RF methods [32][33][34][35] in the development of radiomics models, other studies reported the superior performance of the LASSO or RF classifiers [27,[36][37][38][39]. These divergent findings suggest that the choice of machine learning model influenced the predictive performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, certain radiomic features, such as Skewness, Kurtosis, Range, and GLCM, have shown associations with bone density and osteoporosis [37]. Furthermore, research indicates that CT radiomics features can differentiate between significant RANKL status, a crucial pathway in bone modeling [38]. Zhang W et al underscores the role of the bone metastasis in the formation of secondary metastasis, as evidenced by the progression of PCa cells from primary bone metastasis, tracked using an evolving barcode system [39].…”
Section: Discussionmentioning
confidence: 99%